2011
DOI: 10.1086/658329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pulsed-Xenon Ultraviolet Room Disinfection Device for Impact on Hospital Operations and Microbial Reduction

Abstract: This study evaluated the use of pulsed-xenon ultraviolet (PX-UV) room disinfection by sampling frequently touched surfaces in vancomycin-resistant enterococci (VRE) isolation rooms. The PX-UV system showed a statistically significant reduction in microbial load and eliminated VRE on sampled surfaces when using a 12-minute multiposition treatment cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 7 publications
0
65
0
1
Order By: Relevance
“…Statistically significantly lower bacterial heterotrophic plate counts (HPCs) and no VRE were found in rooms after PX-UV treatment, suggesting that the risk to the next occupant from environmental contamination was correspondingly lower. The study also found that the PX-UV disinfection system is quick enough to be integrated into daily hospital operations without adversely affecting patient throughput (49). Further, the treatment leaves no residual compounds and chemicals behind that can cause ecological problems and/or are potentially harmful to humans.…”
Section: One Technology That Could Potentially Be Used With Traditionmentioning
confidence: 85%
“…Statistically significantly lower bacterial heterotrophic plate counts (HPCs) and no VRE were found in rooms after PX-UV treatment, suggesting that the risk to the next occupant from environmental contamination was correspondingly lower. The study also found that the PX-UV disinfection system is quick enough to be integrated into daily hospital operations without adversely affecting patient throughput (49). Further, the treatment leaves no residual compounds and chemicals behind that can cause ecological problems and/or are potentially harmful to humans.…”
Section: One Technology That Could Potentially Be Used With Traditionmentioning
confidence: 85%
“…8,11 In addition, our study provides 2 assessments not included in previous publications on PX-UV (ie, log reductions achieved by PX-UV on carriers and a comparison with continuous UV). Although the log reductions achieved by PX-UV on carriers at 10 minutes were relatively modest, this exposure time was sufficient to reduce contamination on real-world surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Mercury gas bulbs primarily emit UV-C at 254 nm, whereas xenon gas bulbs produce a broad spectrum of radiation that encompasses the UV (100-280 nm) and visible (380-700 nm) spectra. [8][9][10][11][12] The UV-C radiation emitted by low pressure mercury bulbs is delivered in a continuous stream that gradually accumulates to lethal doses depending on duration of exposure and distance from the primary field of radiation. [1][2][3][4][5][6][7] The broad-range UV delivered by xenon bulbs is emitted in short, high-intensity pulses, possibly requiring a shorter duration of exposure to achieve lethal doses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Germicidal UV irradiation has been shown to be effective in deactivating C. difficile endospores in laboratory and clinical settings (Nerandzic et al, 2010;Rutala et al, 2010;Stibich et al, 2011). Specifically, the UV-C frequency, which ranges from 200 to 280 nm, is known to have germicidal properties through a variety of mechanisms, including photodimerization, photohydration, photo cross-linking, and photoseparation (Rutala et al, 2010;Stibich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%